KUKHARENKOITE-(Ce) AND ITS MINERAL ASSEMBLAGE IN PEGMATITES OF THE VISHNEVYE MOUNTAINS (SOUTH URALS) - V.I. Popova; M.A. Rassomakhin; V.A. Popov; A.M. Kuznetsov; S.M. Lebedeva (Минералогия)
A rare Ba and REE fluorocarbonate kukharenkoite-(Ce) Ba2 Ce(CO3 )3 F with empirical formula (Ba1.88Sr0.17)2.05(Ce0.53La0.31Nd0.11)0.95(CO3 )3 F was found in alkali pegmatite of vein no. 35 in the Vishnevye Mountains, South Urals. Kukharenkoite-(Ce) forms small inclusions up to 3–7 µm in anatase and quartz. Raman spectrum of the studied kukharenkoite-(Ce) is similar to spectrum no. R110190 of kukharenkoite- (Ce) from the RRUFF database. The mineral assemblage of pegmatite from vein no. 35 includes feldspars, annite, yangzhuminite (?), aegirine, magnesio-fluoro-arfvedsonite, allanite-(Ce), ilmenite, monazite-(Ce), anatase, rutile, brookite, titanite, pyrite, molybdenite, calcite, zircon, pyrochlore, and REE carbonates – bastnäsite-(Ce), parisite-(Ce), synchisite-(Ce), röntgenite-(Ce) and huanghoite-(Ce). Kukharenkoite-(Ce) and, mostly likely, yangzhumingite KMg2. 5[Si4 O10]F2 are found for the first time in the Urals.